PENGARUH PENERAPAN TEKNIK DUA TINGGAL DUA TAMU TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTs IBADURRAHMAN LOLO KABUPATEN SOLOK TAHUN PELAJARAN 2012/2013 - Yusuf, Azra Triyana; K, Delsi; Harisman, Yulyanti (STKIP PGRI Sumbar, 2013)
The research was motivated by the studentsâ comprehension of math concept are still low and the student still reluctant to work well in the group. This research aims to determine the studentsâ comprehension of math concept that apply Two Stay Two Stray better than studentsâ comprehension of math concept that apply conventional learning in class VIII MTs Ibadurrahman Lolo Kabupaten Solok. The type of research is experimental by using Randomized Control Group Only Design. The data analysis technique used is T-Test one part the help of MINITAB. The result of hypothesis test obtained P-Value = 0,003 is less than Î± = 0,05, then the hypothesis in this research received. In conclusion, studentsâ comprehension of math concept that apply Two Stay Two Stray type better than studentsâ comprehension of math concept that apply conventional learning.